Influence of Financial Instability and Economic Growth in Foreign Direct Investment in South Africa - Mohammed, Badamasi Sani; Alheety, Sadun Naser Yassin; Al-Hodiany, Zakarya Mohsen (Journal of Developing Economies, 2022)
Purpose: The prime objective of this paper is to study the impact of financial instability (FI) and economic growth (RGDPP) on foreign direct investment (FDI) in South Africa from 1970 to 2016. Methodology: The study used Autoregressive Distributive Lag (ARDL) approach. Evidence from bound test reveals that FI, RGDPP, and FDI are cointegrated in the long run. Findings: The result shows that financial instability and economic growth are positively significant and negatively insignificant influencing the foreign direct investment respectively. Recommendation: The study suggests that government should necessarily develop financial system to let economic growth make a positive contribution to foreign direct investment.